Comparison of Anthocyanin Concentration in Blueberries Processed Using Hydrothermodynamic Technology and Conventional Processing Technologies. Issue 6 (13th July 2014) - Satanina, V.; Kalt, W.; Astatkie, T.; Havard, P.; Martynenko, A.
Abstract Hydrothermodynamic (HTD) processing technology was compared with simulated conventional (SC) processing technology in the production of a blueberry (BB) purée. HTD technology is a single unit operation that combines the physical processes of cavitation, mechanical friction and temperature to create a fruit purée with 100% mass recovery. In HTD processing, frozen wild BBs (Vaccinium angustifolium Aiton) were thawed and pasteurized at 95C to yield a pasteurized purée. In SC processing, BBs were mechanically puréed and pasteurized at the same heating rate as the HTD processing (1.9C/min). BB purées produced with HTD and SC technologies were compared in terms of their anthocyanin (ACN) concentration and percent polymeric color values, which indicate the level of process‐related phenolic oxidation. ACN concentration in purée from both HTD and SC technologies was significantly lower than that in frozen BBs. However, within 48 h after processing, ACN retention (%) in the purée produced using HTD technology was almost two times higher than that in the purée produced using SC processing (81% versus 43% of that in frozen berries). ACN concentration was the highest in the purée produced using HTD when compared with that in commercially available BB‐based products. These results suggest that higher ACN concentration may be achieved in purées produced using HTD technology compared with conventional methods. Practical Applications The potential of hydrothermodynamic (HTD) technology to prevent quality losses of heat‐sensitive blueberry products was evaluated. Anthocyanin retention of blueberry purée processed using HTD technology was significantly higher than that in blueberry products (e.g., juice, purée) processed commercially using thermal processing. This new technology has a great potential for maintaining food quality during product storage by reducing the negative effects of oxygen and prolonged exposure to enzymes.